(untitled) (Orinoquia, 2016)
Cultures with biofloc technology (BFT) are closed intensive aquaculture systems that allow the control of waste through the recycling of nutrients and the formation of bacterial biomass. The objective of this research was to evaluate the effect of the source of protein in the food on the productive performance of white cachama Piaractus brachypomus cultivated in BFT system. Three treatments were evaluated with three repetitions each, as follows: T1: soy cake; T2: soy cake + fish meal and T3: soy cake + spirulina flour, for a total of nine experimental units contained in 500L tanks. Forty-two fish (54.23 ± 10.7g) were seeded per tank, cultivated for 84 days and fed three times a day. For the evaluation of the productive performance, the consumption of food was registered, the fish growth was accompanied by biweekly biometrics and parameters of water quality were determined. At the end of the crop the tanks reached a final average biomass of 15.9 ± 0.8 kg / m3, competitive results compared with other intensive productions in BFT; the daily weight gain was 1.7 ± 0.1 g / day without significant difference between treatments. The feed conversion was found to be around 1.1 ± 0.1 without significant statistical difference between treatments (p <0.05), there was acceptance of the experimental diets and 100% survival in all cases. In the water quality parameters were found average concentrations of ammonium, nitrite and nitrate of 0.1 ± 0.1mg / L, 0.5 ± 0.11mg / L, 195.9 ± 12.91mg / L, respectively, within the ranges acceptable for the species and without significant difference; other parameters such as temperature, oxygen and salinity showed significant differences (P> 0.05) although within the optimum ranges for the culture of the species. It was concluded that the protein source used in the experimental diets did not affect the productive results of the P. brachypomus white cachama cultivated in BFT.